Outcomes of a training video on the shared reading behaviours of caregivers and children. (June 2021) - Coetzee, Tarryn; Moonsamy, Sharon; Neille, Joanne
Despite evidence supporting the implementation of book sharing interventions, few studies have examined the value of providing caregiver training in these contexts. This study draws on the quantitative findings of a larger project that employed a non-randomized comparison group crossover repeated measures design as part of a mixed research approach. The goal of the study was to determine the outcome of a caregiver training video on the book sharing behaviours of 40 caregiver–child dyads in an impoverished peri-urban settlement in South Africa. Children in this study were aged 3 to 6 years of age. Caregivers included older siblings, parents, and other relatives. Findings revealed a significant improvement in caregiver shared reading behaviours in both experimental and comparison groups after viewing the caregiver training video, both within and between groups. The significant change in the shared reading behaviours of the caregivers and children, coupled with the positive impact observed in the children and the cost-effective nature of the intervention, suggest that training videos may constitute an effective intervention medium with the potential to promote children's literacy as a population-based intervention in majority world settings.